The Pan-African High-K I-Type Granites From Batié Complex, West Cameroon: Age, Origin, and Tectonic Implications - Kwékam, Maurice; Talla, Victor; Fozing, Eric Martial; Tcheumenak Kouémo, Jules; Dunkl, István; Njonfang, Eammanuel (Frontiers in Earth Science, 2020)
The Batié granitic massif in western Cameroon is NE-SW elongated, following the regional foliation and parallel to the Kekem-Fotouni shear zone, south-western extension of the Tcholliré-Banyo Fault (TBF). This massif comprises two petrographic units: biotite granite and amphibole granite. Major, trace, REE, Sr-Nd isotopic and new U-Pb data, are used to constrain their nature and origin. The results indicate that they are high-K alkali- calcic with shoshonite affinity. The amphibole granite is metaluminous, whereas biotite granite is weakly peraluminous. Both granites are high temperature I-type granites and crystallized under oxidizing conditions. Initial (87Sr/86Sr)620Ma ratios (0.706-0.708) and εNd620Ma (-12.58 to -8.89) indicate the parental magmas were produced by partial melting of deep old Paleoproterozoic crust and were mixed with felsic magma from upper continental crust. Their TDM typically vary from 1.68 to 1.96 Ga. The massif was mostly emplaced between 630 and 547 Ma; during the transitional period between the crustal thickening (ca. 630-620 Ma) and the development of the shear zones, which began with sinistral movements (613-585 Ma) and continued with dextral movements (585-540 Ma). Plutonism continued during the dextral movements. The Batié granite is geochemically and isotopically similar to other post-collisional pan-African granitic massifs located along TBF.